2008
DOI: 10.1038/jes.2008.49
|View full text |Cite
|
Sign up to set email alerts
|

The attribution of urban and suburban children's exposure to synthetic pyrethroid insecticides: a longitudinal assessment

Abstract: Despite the widespread use of synthetic pyrethroid insecticides that led to common exposure in the population, very few studies have been conducted to quantitatively assess human, particularly, children's, long-term exposures to pyrethroid insecticides. The objective of the Children Pesticide Exposure Study - Washington (CPES-WA) was to establish the longitudinal exposure profiles for pyrethroid insecticides in a cohort of children living in an urban and suburban community using urinary pyrethroid metabolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 23 publications
1
56
0
Order By: Relevance
“…Research has indicated that human can be exposed to pyrethroids or mixtures of pyrethroids in several different types of environmental media (i.e., dust and floor wipes) at home and in consumed foods and beverages. Research has shown that dietary ingestion (food) and nondietary ingestion (dust) are major exposure routes of humans to pyrethroids in this setting (Becker et al, 2006;Lu et al, 2006Lu et al, , 2009Lu et al, , 2010Tulve et al, 2006;Morgan et al, 2007;Fortin et al, 2008;Riederer et al, 2008;Couture et al, 2009;Barr et al, 2010;Koureas et al, 2012;Morgan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that human can be exposed to pyrethroids or mixtures of pyrethroids in several different types of environmental media (i.e., dust and floor wipes) at home and in consumed foods and beverages. Research has shown that dietary ingestion (food) and nondietary ingestion (dust) are major exposure routes of humans to pyrethroids in this setting (Becker et al, 2006;Lu et al, 2006Lu et al, , 2009Lu et al, , 2010Tulve et al, 2006;Morgan et al, 2007;Fortin et al, 2008;Riederer et al, 2008;Couture et al, 2009;Barr et al, 2010;Koureas et al, 2012;Morgan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides are widely used in agriculture and home application (Curwin et al, 2005;Bradman et al, 2007). Both uses pose a potential risk for increased dietary exposure, especially to children (Lu et al, 2009). The synthetic pyrethroid pesticides have been increasingly used, as organophosphate pesticides have been restricted (USEPA, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile phases consisting of mixtures of 0.5 mM NH 4 OAc in methanol/0.5 mM NH 4 OAc in water were used in both instruments, and a volume of 20 or 50 lL was injected in TQD and QTOF, respectively. Separation was performed on an Acquity UPLC BEH C 18 column (10062.1 mm, id 1.7 lm) (Waters, MA, USA) using a gradient elution at a flow rate of 0.3 mL/min.…”
Section: Instrumentationmentioning
confidence: 99%
“…In phosmet experiments, conventional HPLC was used: Discovery C 18 column (5062.1 mm id, 5 lm) (Supelco, Bellefonte, PA); similar gradient elution with 0.5 mM NH 4 OAc in methanol/0.5 mM NH 4 OAc in water.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation